Education and Proto Language Maintenance at Orang Rimba in Jambi Province - Rozelin, Diana; Fauzan, Umar (Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2020)
This research discussed education and dialectology, examining the relation of Orang Rimba (OR) isolect in three places at Jambi Province. Different levels of education in each group of OR also influence language maintenance at proto-language. Language shift will occur when OR communicate with the villagers. The number of OR children who go to school does not guarantee a language shift. This study's benefit was to find out the proto vocabulary that still maintenance and shifted, to know the status of isolect from each group of OR to find out their kinship relations, and to know that education levels may not always affect vocabulary shifts. Dialectometry formula used from Guitar, Proto Austronesian (PAN) used theory from Wurm and Wilson, Proto Malayic (PM) used opinion from Adelaar. This study used qualitative and quantitative to answer different formulation of the problems. The result was: firstly, lexically and phonologically, the status of OR isolect in Jambi, including three regencies consisted of two dialects, four subdialects, and four speeches. There were 5 proto vocals and 19 proto consonants phonemes of OR in Jambi Province. The result of affixation identification at PM *tAr-; *mAN-; *(mb)Ar-; *-an; and *kA-an found innovation and no relic. Secondly, the reflex of PAN and PM at OR Malay dialect having the highest value in maintaining its proto-language (relics) occurred in DP 5,6 Muaro Jambi Regency. Thirdly, the number of children attending school in the villages of Nebang Parah and Nyogan was higher compared to other OR groups. The number of children attending school was in line with the high percentage of proto-languages used.